Development of Soft Skills and Hard Skills of Vocational High School Students Towards Students' Readiness in the World of Work - Wahyu Dwi Handari; Tuwoso Tuwoso (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study discusses the importance of developing soft skills and hard skills for vocational high school students in preparing themselves to enter the workforce. Soft skills, such as communication, teamwork, and leadership, are considered key factors in creating a productive and harmonious work environment. Meanwhile, hard skills, which include specific technical abilities, are the main foundation in carrying out operational tasks. The combination of these two types of skills not only improves work efficiency but also allows the workforce to adapt quickly to changes and challenges in various industrial sectors. This study emphasizes that although hard skills are often the main focus, soft skills have an equally important role in supporting long-term career success. This study also identifies various effective strategies for developing both types of skills, including practice-based training, mentoring, and the use of technology in learning. The results of the study indicate that the integrated development of soft skills and hard skills can increase the productivity and competitiveness of the workforce in the era of globalization and digital transformation.